Spatial distribution and health implications of particulate matter concentrations across diverse land use types in Dinajpur District, Bangladesh - Ahmad Kamruzzaman Majumder; Kazi Khaled Mahmud; Marziat Rahman; Md. Nasir Ahmmed Patoary; Sneha Gautam; Kaspia Rahman Tanima (Geosystems and Geoenvironment)
This study investigates the concentrations of particulate matter (PM1, PM2.5 and PM10) across various land use types in Dinajpur District, Bangladesh, highlighting significant spatial variations in PM concentrations in sensitive, residential, mixed, commercial, road intersection, industrial, and village areas. Along with this, examines the health consequences linked to increased levels of particulate matter (PM).The investigation was carried out in sites within the area of Dinajpur district town, utilising a portable Air Quality Monitor, Portable Air Quality Detector (Model: DM106) and Garmin ETrex 10. To examine and illustrate the differences in pollutant concentrations among various locations, whisker box plots and descriptive statistics were used. Likewise, ArcGIS software was used for spatial analysis, and a dendrogram plot was created to classify and interpret data clusters, providing a deeper understanding of the spatial distribution of pollutants. PM2.5 levels in worst affected sensitive area, Dinajpur General Hospital (77.00 µg/m³), exceeded the Bangladesh National Ambient Air Quality Standards (NAAQS) level (65 µg/m³) by 1.18 times and WHO standards (25 µg/m³) by 3.08 times. Besides, residential areas like Gabgash Residential (78.50 µg/m³) showed PM2.5 concentrations 1.20 and 3.14 times higher than NAAQS and WHO standards respectively. Moreover, commercial zones, particularly around AB Bank, exhibited the highest pollution levels with PM2.5and PM10 concentrations 2.44 and 1.28 times higher than NAAQS norms, respectively. However, road intersections such as Bahadur Mor (113.25 µg/m³) recorded PM2.5 concentrations 1.74 times higher than NAAQS while industrial areas like Sonali Brick Field showed PM2.5 levels exceeding NAAQS by 1.46 times.Finally, the study calculated an Attributable Mortality value of 892 owing to PM2.5, highlighting the significant impact of particle pollution on human health in Dinajpur Sadar. These findings contribute to the understanding of local air quality patterns, emphasizing the critical need for targeted interventions to protect public health and reduce exposure to harmful particulate matter in Dinajpur District.